THE ROLE OF DRUM DRYERS IN DRYING SILICATE MATERILS (Proceedings of International Educators Conference, 2024)
This article explores the significance of drum dryers in the drying process of silicate materials. Silicate materials, commonly found in various industries, pose unique challenges in terms of moisture removal. Drum dryers, known for their efficiency and versatility, play a crucial role in addressing these challenges. The article presents a comprehensive analysis of the literature, discusses the methods employed in the drying process, presents results obtained from using drum dryers, and concludes with insights and suggestions for further research.